Information System Effectiveness Analysis Accounting For Receipts, Recording and Financial Reporting At Cv. Bina Puskud Mandiri - Hasibuan, Vania Adisty Hasibuan; Rama Gita Suci (Islamic Business and Management Journal, 2025)
This study was conducted with the aim of determining the accounting information system for cash receipts, recording and reporting at CV Bina Puskud Mandiri. The research approach used a qualitative descriptive type with interview methods, observation, documentation and previous research results. The results of the study indicate that the accounting information system for cash receipts, recording and reporting at CV Bina Puskud Mandiri is carried out manually and computerized. Manually, it is done by recording sales recaps on cash vouchers and computerized by using Microsoft Excel in sales recaps, journals and financial reports. Using Microsoft Excel in cash receipts, recording and reporting requires more time and greater effort in accuracy so that there are no errors that can harm CV Bina Puskud Mandiri.